“Employee Well-Being In The Context Of Uncertainty And Change : Implications For HRD” (2017) – Advances In Developing Human Resources - sephianabayhaqi; Maimunah Maimunah; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Employee wellbeing in an uncertain environment is an increasingly relevant topic in the modern world of work. Today's business environment is often characterized by rapid change, complexity, and complexity that can affect employees' mental as well as physical health. This research aims to investigate methods that can improve employee welfare in threatening situations. Where feelings around them can influence stress, job satisfaction and also the level of employee engagement. This research also explains how HRD can deal with this problem. This research uses a type of library research, namely a series of activities related to library data collection methods. The results of this research can provide valuable insight for companies in improving employee welfare in a work environment where problems are very widespread.